Problems Pertaining Local-Type Fuel Burning in Boilers with Spreader Stoker - N. V. Karnitsky; S. M. Zamarа (Известия высших учебных заведений и энергетических объединенний СНГ: Энергетика, 2011)
The paper considers problems arising in case of burning local-type fuels in pilot boilers with spreader stokers. Some solutions and proposals permitting to increase efficiency of fuel-burning units are given in the paper.